Development in building fire detection and evacuation system-a comprehensive review - Gajanand S. Birajdar; Rajesh Singh; Anita Gehlot; Amit Kumar Thakur (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Fire is both beneficial to man and his environment as well as destructive and deadly among all the natural disasters. A fire Accident occurs very rarely, but once it crops up its consequences will be devastating. The early detection of fire will help to avoid further consequences and saves the life of people. During the fire accidents, it is also important to guide people within the building to exit safely. Because of this, the paper gives a review of literature related to recent advancements in building fire detection and emergency evacuation system. It is intended to provide details about fire simulation tools with features, suitable hardware, communication methods, and effective user interface.